Acute myocardial infarction shortly after valve-in-valve transcatheter aortic valve implantation successfully managed with challenging percutaneous coronary intervention - Kenan Yalta; Çağlar Kaya; Yüksel Aksoy; Mustafa Yılmaztepe; Fatih Kardaş (KARE Publishing, 2018)
In recent years, transcatheter aortic valve implantation (TAVI) has been considered a novel option for the management of surgically high-risk patients requiring aortic valve replacement. Presently described is a case of acute coronary syndrome (ACS) managed with a challenging primary percutaneous coronary intervention (PCI) shortly after a valve-in-valve TAVI intervention. This case highlights 2 important issues: PCI may be an option for the management of coronary heart disease in patients after TAVI even in the setting of demanding features associated with coronary osteal engagement, and secondly, TAVI may serve as a potential risk factor for future coronary ischemic syndromes, largely due to its potential adverse effects on coronary flow dynamics, etc. However, the latter notion is quite speculative, and should be tested in further studies.